2023
DOI: 10.1186/s12885-023-10784-8
|View full text |Cite
|
Sign up to set email alerts
|

First-line atezolizumab/durvalumab plus platinum–etoposide combined with radiotherapy in extensive-stage small-cell lung cancer

Abstract: Background Immunotherapy has made significant advances in the treatment of extensive-stage small-cell lung cancer (ES-SCLC), but data in combination with radiotherapy are scarce. This study aims to assess the safety and efficacy of chemoimmunotherapy combined with thoracic radiotherapy in patients with ES-SCLC. Methods This single-center retrospective study analyzed patients with ES-SCLC who received standard platinum–etoposide chemotherapy combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Diamond et al performed a single-arm retrospective study enrolling 20 patients and found favorable safety profile and improved OS (median OS) with the use of TRT and ICIs plus CHT in the management of ES-SCLC [ 45 ]. Another single-arm retrospective analysis included 36 patients also suggested that combined with TRT in the first-line treatment was safe and had ample survival benefits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diamond et al performed a single-arm retrospective study enrolling 20 patients and found favorable safety profile and improved OS (median OS) with the use of TRT and ICIs plus CHT in the management of ES-SCLC [ 45 ]. Another single-arm retrospective analysis included 36 patients also suggested that combined with TRT in the first-line treatment was safe and had ample survival benefits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no conclusion was reached regarding ES-SCLC. Some studies thought ICIs plus radiotherapy could prolong survival ( 36 , 37 ), but the toxicity caused by radiation plus ICIs can limit this function ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…But a retrospective study including 41 patients with ES-SCLC, 23 patients received 30Gy/10 fractions cTRT after systemic therapy and 18 patients did not receive cTRT, showed that cTRT significantly improved OS compared with systemic therapy only group (1-year OS 78.6% vs. 39.7%, p=0.019 ( 39 ). Furthermore, several single-center retrospective studies have also demonstrated a survival benefit of cTRT after first-line chemoimmunotherapy ( 40 , 41 ). Given that all existing studies are retrospective, the role of cTRT in ES-SCLC in the immunotherapy era should be interpreted with caution, and we look forward to the prospective study results.…”
Section: The Consolidative Thoracic Radiotherapymentioning
confidence: 99%
“…A real-world study showed that cTRT after first-line chemoimmunotherapy did not increase the incidence of adverse events compared with systemic therapy alone ( 41 ). A retrospective study involving 36 patients with ES-SCLC who received first-line chemoimmunotherapy followed by cTRT at 60Gy/28 fractions in most patients, showed that 8% of patients developed radiation-related pneumonitis, all of which were grade 1-2, and four patients discontinued immunotherapy after immune-related pneumonitis but completed cTRT ( 40 ). Thus, cTRT has a survival benefit and can be tolerated.…”
Section: The Consolidative Thoracic Radiotherapymentioning
confidence: 99%